2018
DOI: 10.4103/jrms.jrms_413_16
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of extracorporeal shockwave therapy for chronic Achilles tendinopathy: A randomized clinical trial

Abstract: Background:In this study, we aimed to evaluate the effectiveness of extracorporeal shockwave treatment (ESWT) on pain and ankle-hindfoot scale of the American Orthopedic Foot and Ankle Society (AOFAS) score of patients with chronic Achilles tendinopathy (AT).Materials and Methods:In this double-blind clinical trial, 43 patients with chronic AT were selected and randomly allocated in two groups to receive a basic treatment with ESWT or sham SWT (radial and focused shock waves, four sessions once a week for 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…In measures where higher scores indicate more favorable outcomes, ESWT was associated with higher VISA-A score than comparison treatment (MD, 1.53; 95% CI, 0.69 to 2.37; P = .0003; I 2 = 92%) ( Figure 6 ) 10 12 , 16 and with higher AOFAS score (MD, 1.35; 95% CI, 0.28 to 2.41; P = .01; I 2 = 93%) ( Figure 7 ). 9 , 15 , 16 The 2 groups did not differ significantly in tenderness score (MD, –0.25; 95% CI, –0.77 to 0.27; P = .34; I 2 = 61%) ( Figure 8 ) 11 , 13 or pain threshold (MD, 0.45; 95% CI, –0.30 to 1.20; P = .24; I 2 = 81%) ( Figure 9 ). 10 , 12 …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In measures where higher scores indicate more favorable outcomes, ESWT was associated with higher VISA-A score than comparison treatment (MD, 1.53; 95% CI, 0.69 to 2.37; P = .0003; I 2 = 92%) ( Figure 6 ) 10 12 , 16 and with higher AOFAS score (MD, 1.35; 95% CI, 0.28 to 2.41; P = .01; I 2 = 93%) ( Figure 7 ). 9 , 15 , 16 The 2 groups did not differ significantly in tenderness score (MD, –0.25; 95% CI, –0.77 to 0.27; P = .34; I 2 = 61%) ( Figure 8 ) 11 , 13 or pain threshold (MD, 0.45; 95% CI, –0.30 to 1.20; P = .24; I 2 = 81%) ( Figure 9 ). 10 , 12 …”
Section: Resultsmentioning
confidence: 94%
“…In measures where lower scores indicate more favorable outcomes (VAS pain, Roles and Maudsley, NRS, and Likert scores), ESWT was associated with lower VAS scores than comparison treatment (MD, –2.14; 95% CI, –2.73 to –1.56; P < .001; I 2 = 88%) ( Figure 2 ) 10 , 12 , 15 , 16 as well as with lower Roles and Maudsley score (MD, –2.80; 95% CI, –3.30 to –2.30; P < .001; I 2 = 69%) ( Figure 3 ) based only on 2 studies. 5 , 6 ESWT was also associated with lower NRS score (MD, –0.58; 95% CI, –1.07 to –0.08; P = .02; I 2 = 69%) ( Figure 4 ) 10 12 and lower Likert scale score (MD, −0.46; 95% CI –0.87 to –0.05; P = .03; I 2 = 55%) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notranicola et al [ 14 ] recruited patients with symptom duration over 6 months, and 2 months after shock wave therapy, AOFAS raised to only 73 ± 22.9. On the contrary, Vahdatpour et al [ 20 ] observed patients of 4.5 months in disease duration; AOFAS reached as high as 85.85 ± 7.8 at 16 weeks after ESWT. Similarly, Pavone et al [ 29 ] enrolled patients with disease course over 3 months for research, combined with eccentric exercise, AOFAS scores were achieved as 85.2 ± 4.1.…”
Section: Discussionmentioning
confidence: 97%
“…Epidemiologically, in term of gender tendency, some authors believe that CAT influences more male patients than the female [ 12 ], which possibly be related to more frequent physical activities in male exerciser. In fact, a slightly higher incidence of female patients, about 53-59% [ 13 19 ], was reported in the majority of literatures, even as high as 77.4% or 81.8% [ 11 , 20 ] was mentioned. In our study, the general rate of female patient is 53.3% (35/66) and slightly higher than male, which is consist with most of articles.…”
Section: Discussionmentioning
confidence: 99%
“…Current recommended treatment for those with persistent Achilles tendinopathy emphasizes tendon-loading exercises and activity modification/education [1,12] with eventual referral to surgery for severe long-standing cases [13,14]. Placebo-controlled studies of proposed adjunct treatments such as shockwave therapy [15][16][17] or topical glyceryl trinitrate [18,19] have not clearly demonstrated a benefit for Achilles tendinopathy, showing small improvements [16], improvements reported by a single study [19], or no apparent benefit [15,17,18]. There are very few placebo-controlled studies of injection therapies [20][21][22][23][24][25][26] or analgesics (either topical [27] or oral [28]) to inform clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%